2015
DOI: 10.1590/s0100-204x2015000800006
|View full text |Cite
|
Sign up to set email alerts
|

Produção de matéria seca e controle de plantas daninhas por leguminosas consorciadas com cana-de-açúcar em cultivo orgânico

Abstract: Resumo -O objetivo deste trabalho foi avaliar a produção de matéria seca e o controle de plantas daninhas por espécies de leguminosas consorciadas com cana-de-açúcar, em cultivo orgânico. As espécies leguminosas Arachis pintoi, Cajanus cajan, Calopogonium mucunoides, Crotalaria anagyroides, Crotalaria juncea e Stylosanthes 'Campo Grande' foram semeadas em novembro de 2012, nas entrelinhas da cana-de-açúcar. O delineamento experimental em blocos ao acaso foi utilizado com quatro repetições e dois controles -um … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
(18 reference statements)
1
8
0
8
Order By: Relevance
“…The practice of green manuring has been shown to be important for different crops, whether they use intercropping or crop rotation systems. This is due to the innumerable benefits provided by this practice, such as the improvements in the physical, chemical and biological aspects of soil, increased productivity, and weed control Dantas et al, 2015;Tao et al, 2017). However, few studies have shown the influence of green manures on the yield and quality of organic foods such as tomatoes.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of green manuring has been shown to be important for different crops, whether they use intercropping or crop rotation systems. This is due to the innumerable benefits provided by this practice, such as the improvements in the physical, chemical and biological aspects of soil, increased productivity, and weed control Dantas et al, 2015;Tao et al, 2017). However, few studies have shown the influence of green manures on the yield and quality of organic foods such as tomatoes.…”
Section: Introductionmentioning
confidence: 99%
“…2017 Ambrosano et al, 2013). Intercropping usually results in biomasses in the lower part of this range (Blaise et al, 2005a;Dantas, 2015) The greater biomass of sunnhemp treatments contributed to their higher nutrient recycling than that of pigeon pea, in spite of higher dry matter concentrations of N and P in pigeon pea ( Table 1). The contribution of nitrogen was particularly important, part of which may have come from symbiotic N 2 fixation (Perin et al 2006, Espana et al 2006Faria et al, 2007) which could lead to net increases in soil N availability.…”
Section: Resultsmentioning
confidence: 99%
“…The period of growth is another important variable controlling productivities of green manures. Pigeon pea hasa slower initial growth than sunnhemp(Blaise et al, 2005b;Dantas, 2015).…”
mentioning
confidence: 99%
“…Machado e Margarido (2014) constataram que o consórcio de canade-açúcar com diferentes culturas (milho, feijão e mandioca) não influenciou a altura da cana e o Grau Brix. Dantas et al (2015) observaram que as leguminosas amendoim forrageiro (Arachis pintoi), calopogônio (Calopogonium mucunoides), xiquexique (Crotalaria anagyroides), crotalária júncea (Crotalaria juncea), estilosantes 'Campo Grande' (mistura física de sementes de Stylosanthes capitata e S. macrocephala) e guanduanão (Cajanus cajan), introduzidas nas entrelinhas da cana de açúcar, em manejo orgânico, em sistema de consorciação, com semeadura tardia dos adubos verdes, não interferem na produtividade de colmos, produção de açúcar e qualidade do caldo da cana planta e da primeira cana soca.…”
Section: Resultsunclassified